Network analysis of drug side effects and indications / Yousoff Effendy Mohd Ali - Yousoff Effendy, Mohd Ali (2018)
This thesis aims to understand drug relationship based on drug side effect and indication through network analysis. Two drug networks are constructed using the SIDER 4.1 dataset which are (a) drug-side effect network and (b) drug-indication network. These networks have been analyzed using network analysis to describe the element-level and network-level properties. Various measurements in network analysis are used to describe those properties including centralities, HITS, PageRank and Burt’s constraint. Based on the node measurements in network analysis, all drugs in the networks were ranked and a few prominent drugs have been identified in both networks. The prominent drugs were used to explain the application of network analysis on finding or predicting potentially new uses of drugs called drug repositioning. Interestingly, some of the prominent drugs were appeared in list of successful drug repositioning and some of the predicted new uses were already appeared in current clinical studies.